Risk and Uncertainty in Monetary Policy - Greenspan, Alan (American Economic Review, 2004)
I plan to sketch the key developments of the past decade and a half of monetary policy in the United States from the perspective of someone who has been in the policy trenches. I will offer some conclusions about what I believe has been learned thus far, though I suspect, as is so often the case, the passing of time, further study, and reflection will deepen our understanding of these developments. This is a personal statement; I am not speaking for my current colleagues on the Federal Open Market Committee (FOMC) or the many others with whom I have served over these many years. The tightening of monetary policy by the Federal Reserve in 1979, then led by my predecessor Paul Volcker, ultimately broke the back of price acceleration in the United States, ushering in a two-decade long decline in inflation that eventually brought us to the current state of price stability. The fall in inflation over this period has been global in scope, and arguably beyond the expectations of even the most optimistic inflationfighters. I have little doubt that an unrelenting focus of monetary policy on achieving price stability has been the principal contributor to disinflation. Indeed, the notion, advanced by Milton Friedman more than 30 years ago, that inflation is everywhere and always a monetary phenomenon, is no longer a controversial proposition in the profession. But the size and geographic extent of the decline in inflation raises the question of whether other forces have been at work as well. I am increasingly of the view that, at a minimum, monetary policy in the last two decades has been operating in an environment particularly conducive to the pursuit of price stability. The principal features of this environment included (i) increased political support for stable prices, which was the consequence of, and reaction to, the unprecedented peacetime inflation in the 1970’s, (ii) globalization, which unleashed powerful new forces of competition, and (iii) an acceleration of productivity, which at least for a time held down cost pressures. I believe we at the Fed, to our credit, did gradually come to recognize the structural economic changes that we were living through and accordingly altered our understanding of the key parameters of the economic system and our policy stance. The central banks of other industrialized countries have grappled with many of the same issues. But as we lived through it, there was much uncertainty about the evolving structure of the economy and about the influence of monetary policy. Despite those uncertainties, the trauma of the 1970’s was still so vivid throughout the 1980’s that preventing a return to accelerating prices was the unvarying focus of our efforts during those years. In recognition of the lag in monetary policy’s impact on economic activity, a preemptive response to the potential for building inflationary pressures was made an important feature of policy. As a consequence, this approach elevated forecasting to an even more prominent place in policy deliberations. After an almost uninterrupted stint of easing from the summer of 1984 through the spring of 1987, the Fed again began to lean against increasing inflationary pressures, which were in part the indirect result of rapidly rising stock prices. We had recognized the risk of an adverse reaction in a stock market that had recently experienced a steep run-up—indeed, we actively engaged in contingency planning against that possibility. * Board of Governors of the Federal Reserve System, 20th Street and Constitution Avenue, N.W., Washington, DC 20551. 1 I, nonetheless, wish to thank my colleagues David Stockton, David Wilcox, Don Kohn, Ben Bernanke, and John Taylor, for their many suggestions and reminiscences.